2015
DOI: 10.1017/s0033291715001956
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression and anxiety predicts the pattern of offspring symptoms during their transition to adulthood

Abstract: BackgroundEpisodes of depression and anxiety (D&A) during the transition from late adolescence to adulthood, particularly when persistent, are predictive of long-term disorders and associated public health burden. Understanding risk factors at this time is important to guide intervention. The current objective was to investigate the associations between maternal symptoms of D&A with offspring symptoms during their transition to adulthood.MethodData from a large population-based birth cohort study, in South Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 23 publications
(43 reference statements)
3
21
0
1
Order By: Relevance
“…It is known that maternal well-being is important for child development, especially in children younger than 3 years who are vulnerable and dependent on their mothers for care, nutrition and stimulation [Singla et al, 2015]. Also, depressed mothers could produce a marked effect on their children concerning depression in childhood and adolescence, negatively impacting chronic disease development [Gonçalves et al, 2016]. A possible explanation for the higher caries prevalence observed in children from depressed mothers free of caries, when compared to children from caries-free mothers but without depression symptoms, could be related to the fact that depression is a disease where the individuals are focused on their own feelings and thoughts, leaving the other in the background [Coelho et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that maternal well-being is important for child development, especially in children younger than 3 years who are vulnerable and dependent on their mothers for care, nutrition and stimulation [Singla et al, 2015]. Also, depressed mothers could produce a marked effect on their children concerning depression in childhood and adolescence, negatively impacting chronic disease development [Gonçalves et al, 2016]. A possible explanation for the higher caries prevalence observed in children from depressed mothers free of caries, when compared to children from caries-free mothers but without depression symptoms, could be related to the fact that depression is a disease where the individuals are focused on their own feelings and thoughts, leaving the other in the background [Coelho et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Parents, especially mothers, are widely acknowledged to play a pivotal role in the establishment of oral health-promoting behaviors that prevent the development of childhood dental caries [Hooley et al, 2012]. Maternal depression and anxiety are related to their children's depression episodes during childhood and adolescence, especially in females, and the persistent symptoms are predictive of long-term disorders [Gonçalves et al, 2016]. Parental psychosocial factors that have been shown to negatively affect child oral health include maternal depression, low sense of coherence, indulgent parenting, and parental stress [LaValle et al, 2000;Quiño-nez et al, 2001;Bonanato et al, 2009;Seow et al, 2009].…”
mentioning
confidence: 99%
“…Maternal psychological conditions clearly have an influence in whole life of children and attitudes in relation to care and the context that mothers are living have been closely associated to children's oral health . Previous studies have shown that psychological condition, such as depression, can result in inadequate oral health care, and a relationship between maternal depression and anxiety and children's oral health was also found .…”
Section: Introductionmentioning
confidence: 99%
“…The mother's depression can negatively affect the establishment of the first interactions with the child. Also, maternal depression can produce a market effect on their children depression in childhood and adolescence, negatively impacting in chronic disease development. Considering that maternal depression could have long‐term detrimental effects on the offspring mental health and that psychological disorders are associated with SB in children, it is possible to assume that preschoolchildren from mothers presenting depression could also develop emotional defense mechanisms, allowing for the onset of parafunctional habits such as teeth grinding and clenching.…”
Section: Discussionmentioning
confidence: 99%